Online Shop Trends For Women Entrepreneurs In Improving The Family Economy - Meci Nilam Sari; Nadia Angraini; Azmen Kahar; Rika Septrizarty; Dabitha Wise Maliha (Departement of Mathematics Education, 2023)
Women entrepreneurs are one of the factors driving the household economy, because women entrepreneurs have a tenacious and persistent nature, have creativity, motivation, and innovation which can later advance MSMEs in Indonesia. Women entrepreneurs make a significant contribution to the economy in terms of job creation, skills development, and poverty alleviation. Entrepreneurs are able to compete with male entrepreneurs. By utilizing existing social media, women entrepreneurs are more innovative, creative, and efficient in using their time and are able to balance their time between work, household and also the business they run. Social media, e-commerce make them sell more of the items they promote with online shop trends in the digital marketing world.